Studing the effects of a combined adiponectin-metformin on glucose and lipids levels with anti-ulcerogenic activity of adiponectin against ethanol induced gastric mucosal injury in rat blood / Atieh Abdollahi Fard - Fard, Atieh Abdollahi (2011)
Adiponectin is a protein hormone secreted entirely by abdominal fat tissue. It has anti-diabetic, antiatherogenic and anti-inflammatory effects. The present study was performed to evaluate the effects of a combination of adiponectin with metformin on blood glucose, TG (triglyceride), CHOL (Total cholesterol), LDL (Low density lipoprotein) and HDL (High density lipoprotein) in mice and also to evaluate the anti-ulcerogenic activity of adiponectin against ethanol induced gastric mucosal injury in rats. Three groups of female ICR healthy mice were gavaged with 1% volume / body weight high fat-sucrose. Metformin in a dosage of 250mg/kg was added to the feed and a dosage of 2.5mg/kg adiponectin was injected intraperitoneally. Blood glucose was measured at one hour intervals for 5 hours. Blood concentrations of TG, CHOL, LDL and HDL were also measured at the end of the fifth hour of the experiment. On the other hand, four groups of adult albino Wistar rats were intraperitonially injected with distilled water, omeprazole 20mg/kg body weight, 1.25mg/kg and 2.5mg/kg adiponectin one hour before oral administration of absolute ethanol to generate gastric mucosal injury. An hour after the oral intakes of absolute ethanol the rats were sacrificed and the ulcer areas of the gastric walls were determined. The results indicate that the effect of a combination of metformin and adiponectin on blood glucose and HDL is considerably effective, but made no significant difference on TG, LDL and CHOL levels. Moreover, histological studies of the gastric wall of negative control rats revealed severe damage of gastric mucosa, along with edema and leucocyte infiltration of the submucosal layer compared to rats pre-treated with either omeprazole or adiponectin extract where there was marked gastric protection along with reduction or inhibition of edema and leucocyte infiltration of the submucosal layer. In conclusion, the present findings suggest that a combination therapy with metformin plus adiponectin is probably attributable to the natural cause of type 2 diabetes rather than to the effect of therapy itself, and also, adiponectin promotes ulcer protection as ascertained by the comparative decrease of inflammation ulcer areas, reduction of edema and leucocyte infiltration of the submucosal layer.